Menggali Potensi Road-Map Reformasi Birokrasi di Kabupaten Bima Pasca-PermenPAN-RB Nomor 3 Tahun 2023 - Muhammad Nur; Nike Ardiansyah (Public Service and Governance Journal, 2024)
This study aims to evaluate the impact of bureaucratic reform in Bima Regency following the issuance of the Ministerial Regulation on Administrative Reform (PermenPAN-RB) Number 3 of 2023, with a primary focus on enhancing the quality of public services and the efficiency of administrative processes through the implementation of information technology. Utilizing a qualitative descriptive research method, this study explores the perceptions and experiences of civil servants (ASN), policymakers, and the civilian community in Bima Regency. Data were collected through in-depth interviews, participatory observation, and document analysis to understand the implementation and effectiveness of the reforms undertaken. The findings indicate that bureaucratic reform in Bima Regency has made significant progress in improving the efficiency and effectiveness of public services, underpinned by the Bureaucratic Reform (RB) Index. The main focus of this reform is to accelerate service delivery, enhance user satisfaction, and reduce unnecessary bureaucracy, with the digitalization of services as a key step that has successfully reduced waiting times and increased transparency. Training programs for civil servants have also been enhanced to ensure high-quality services that meet the needs of the community. The roadmap for bureaucratic reform also includes efforts to strengthen integrity and transparency, with an emphasis on improving the Corruption Perception Index (CPI) score through the strengthening of oversight institutions and the implementation of policies that limit direct interactions, reducing opportunities for corruption. Furthermore, Bima Regency continues to innovate by integrating information technology into government administration to improve the Government Effectiveness Index (GEI) and E-Government Development Index (EGDI), ensuring data security, and expanding public access to government services, especially in remote areas.